Induction of peroxisomal oxidases in mussels: comparison of effects of lubricant oil and benzo(a)pyrene with two typical peroxisome proliferators on peroxisome structure and function in Mytilus galloprovincialis - Cancio, Ibon; Orbea, Amaia; Völkl, Alfred; Fahimi, H. Dariush; Cajaraville, Miren P. (Toxicology and applied pharmacology, 1998)
Marine mussels are used as bioindicators of water pollution in marine and estuarine environments in the so-called “Mussel Watch” programs because of their capacity to accumulate numerous organic xenobiotics including aromatic hydrocarbons. In this study, we have analyzed the effects of two xenobiotics [benzo(a)pyrene and the water accommodated fraction of a lubricant oil] and two typical (rodent) peroxisome proliferators (clofibrate and dioctyl phthalate) on structure and function of peroxisomes in digestive glands of musselsMytilus galloprovincialis,either following water exposure (for 1, 7, and 21 days) or after direct injection through the adductor muscle (for 1 and 7 days). The activities of catalase (CAT), acyl-CoA oxidase (AOX), andd-amino acid oxidase were determined in whole homogenates of digestive glands. In addition, stereological methods were applied on sections stained histochemically for demonstration of catalase activity in order to quantify the morphological changes of peroxisomes. The peroxisomal acyl-CoA oxidase andd-amino acid oxidase were increased in mussels injected for 7 days with benzo(a)pyrene, phthalate, and clofibrate and a similar trend was noted for benzo(a)pyrene and lubricant oil in water exposure experiments (21 days). The catalase activity was reduced or unchanged depending on the mode of exposure of animals. By stereology, significant increases of numerical and volume densities of peroxisomes were found in animals injected for 7 days with lubricant oil or clofibrate. These observations indicate that peroxisomal oxidases in mussels are induced at moderate rates in response to different xenobiotics and that their determination could provide a (sensitive) marker for detection of effects of some toxic pollutants, particularly the lubricant oils which in addition induce significant structural alterations of mussel peroxisomes.